Nitric Oxide Modulates Salt Stress Tolerance in Lettuce - Marques, Isabelly Cristina da Silva [UNESP]; Silva, Dayane Mércia Ribeiro; Bispo, Geane Lourenço [UNESP]; Oliveira, Francisco de Assis de; Ono, Elizabeth Orika [UNESP]; Rodrigues, João Domingos [UNESP] (MDPI, 2023)
Crops are constantly threatened by salinity. Nitric oxide (NO) is an attenuating agent for salt stress; however, the specific roles of NO in gas exchange and lettuce production are not well established. The objective of this study was to evaluate the application of different concentrations of sodium nitroprusside (SNP) as an agent to mitigate salt stress in lettuce plants. Lettuce seedlings in pots were subjected to irrigation without and with saline water (0.2 and 3.5 dS m−1) and applications of different concentrations (0, 50, 100, 150, and 200 µM) of SNP, a NO donor. Saline stress negatively affected lettuce development with a reduction of 29.5% in leaf area, 6.3% in relative water content in the leaf, 17.2% in stem diameter, and 10.7% in dry matter mass in the control, but the application of SNP mitigated the deleterious effects of salt stress. Concentrations between 100 and 150 µM of SNP improved the photosynthetic metabolism of lettuce under salinity, with an increase of 46.7% in CO2 assimilation and 42.3% in fresh matter mass. Pearson’s correlation showed that fresh matter correlated positively with CO2 assimilation. Therefore, SNP can be used to mitigate salt stress in lettuce.
Keywords: gas exchange; Lactuca sativaL; salinity; sodium nitroprusside; yield